Neonatal Jaundice and Breast Feeding: A Narrative Review: Penyakit kuning pada bayi baru lahir dan pemberian ASI: Sebuah Tinjauan Naratif - Awad, Kadhim Jawad (Indonesian Journal on Health Science and Medicine, 2024)
A significant proportion of both term and preterm neonates experience neonatal jaundice. Jaundice is the most common cause of readmission to the hospital in otherwise healthy-term infants. Serum bilirubin levels rise due to red blood cell lysis, which is the main cause of jaundice. The blood carries bilirubin as "unconjugated" bilirubin, mostly attached to albumin. Most term babies have "physiological" jaundice, which doesn't require any special care and can be temporarily alleviated with phototherapy. Neonatal frequently experience unconjugated hyperbilirubinemia, which is typically normal, or the result of breast milk jaundice, which is a benign condition. But neonatal jaundice resulting from underlying cholestasis (and the conjugated hyperbilirubinemia that follows) is invariably pathological and requires immediate medical attention. Severe newborn jaundice is comparatively common in developing nations, and these babies are susceptible to bilirubin-induced brain damage Highlights: Neonatal jaundice is common, especially in term and preterm infants. Physiological jaundice is benign; phototherapy often provides temporary relief. Severe jaundice risks brain damage, needing urgent care, especially in cholestasis. Keywords: Neonatal Jaundice, Mothers, Narrative Review